MENINGKATKAN KESADARAN PAJAK PADA UMKM: MENGATASI FENOMENA ECONOMY SHADOW - Anggraeni, Ary Yunita; Santi, Fitriana; Puspita, Wulan Dri; Agesia, Sheina Vella (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2026)
Micro, Small, and Medium Enterprises (MSMEs) are often perceived as small-scale businesses; however, they in fact hold a strategic role in driving the national economy. Due to their significant contribution, MSMEs have increasingly become the target of tax policies, including reporting and payment obligations. Unfortunately, many MSME actors still lack an understanding of their tax responsibilities and the importance of legal tax planning. This community service program aimed to provide knowledge related to tax obligations and strategies for proper tax planning to MSMEs under the guidance of BAZNAS. The program was carried out on September 2, 2025, involving 10 potential MSMEs. The results indicate an improvement in MSMEs’ understanding of tax obligations, marked by the initiation of more disciplined financial record-keeping practices.